REINTERPRETASI HADIS ERA KONTEMPORER: APLIKASI HERMENEUTIKA HANS-GEORG GADAMER DALAM MEMECAH KEBEKUAN MAKNA - Rukmana, Fachruli Isra; Abror, Robby Habiba (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2023)
The use of the narrative of lying in the name of the Prophet by orthodox hadith scholars has made hadith a boring scholarly product that lags behind the study of the Qur'an. This has stigmatised the hadith as a more authoritative text than the Qur'an. This paper addresses three issues: First, what is the development of hadith interpretation in the modern world? Second, what contexts must be updated in the study of hadith? Third, how to apply Gadamer's hermeneutics as a development of interpretation to the study of hadith. This research is qualitative research with a library research approach. Distinctively, this research focuses on two data models, namely primary and secondary data. The results of this study show that providing new interpretations of hadith is not a form of lying on behalf of the Prophet. As an authoritative source of Islamic law, the understanding of the hadith must always be forced to issue new knowledge like the Qur'an, which is always explored with various approaches to get a meaning from the current context. The methods developed by revisionist scholars provide brilliant ideas and make the study of sacred texts more lively and dynamic. Therefore, Hans-Georg Gadamer's hermeneutics is the most valid reference in giving a new direction for studying hadith understanding in the modern world